2014
DOI: 10.1590/s0100-55022014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Aproveitamento teórico-prático da disciplina anatomia humana do curso de fisioterapia

Abstract: A Anatomia Humana estuda as estruturas do corpo humano e as relações entre elas. Assim, seu ensino a estudantes da área da saúde, incluindo alunos de Fisioterapia, é de extrema importância. É necessário um bom aproveitamento nesta disciplina para se tornar um bom profissional, porém as estratégias de ensino-aprendizagem nesta disciplina têm sido bastante discutidas. Com base nesta premissa, este estudo teve por objetivos avaliar o aproveitamento teórico-prático dos discentes do curso de Fisioterapia na discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
2
5
0
4
Order By: Relevance
“…The results of this experience indicated no difference regarding the proportion of failure between the conventional and TBL groups. These findings confirm previous studies in the literature which, regardless the teaching method, students try to be approved, using memorization techniques and focus on the study on the day before the tests [9,25]. Therefore, the traditional teaching method seems not to favor the proportion of approval, but some influence was seen from the way the content is taught and learned.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this experience indicated no difference regarding the proportion of failure between the conventional and TBL groups. These findings confirm previous studies in the literature which, regardless the teaching method, students try to be approved, using memorization techniques and focus on the study on the day before the tests [9,25]. Therefore, the traditional teaching method seems not to favor the proportion of approval, but some influence was seen from the way the content is taught and learned.…”
Section: Discussionsupporting
confidence: 88%
“…Monitoring of Human Anatomy supplies essential assistance for the construction of a qualified professional, since the lack of notions of this discipline, prevents the physiotherapist job in examining, diagnose and treat his patient (ARRUDA and SOUSA, 2014). Thus, it corroborates the reports lectured by student-monitors in this study.…”
Section: Professional Contributionsupporting
confidence: 81%
“…Our data corroborate the study of Rozendo et al [19] regarding teaching methods and the most used teaching resources, which observed in their study that (86.2%) of teachers affirmed to make use of the lecture as teaching method followed by case discussion (48.3%), laboratory practice class (41.4%), clinical practice class (34.5%) and seminary (27.6%). According to Arruda and Sousa [26], it is that the teaching of Anatomy has been effected by reproductive practices, in which the apprehension of knowledge is merely mechanical, and that assessments are usually organized in two stages: a theoretical test, centered in the definition of functions of different organs and systems, and another practice, in which students, in most cases, have to identify anatomical structures previously marked. In the specific case of this discipline, mechanical learning is necessary, but simply memorizing the names of anatomical structures is not enough.…”
Section: Discussionmentioning
confidence: 99%